Mechanical characterization of blends containing recycled paper pulp and other lignocellulosic materials to develop hydromulches for weed control. (March 2020) - Claramunt, Josep; Mas, M. Teresa; Pardo, Gabriel; Cirujeda, Alicia; Verdú, Antoni M.C.
Abstract : Spreading of hydromulch as a crop management technique might show important advantages over plastic films for weed control, because it can be applied anywhere in a field, even in orchard and vineyard rows. In the present work, 24 blends were prepared by mixing paper pulp, from recovered paper and cardboard coming from paper mills, with different additives: (a) wheat straw, rice hulls, and substrate used for mushroom cultivation on the one hand as fillers, and (b) rice bran, white glue, sodium silicate, and powered gypsum on the other hand as agglomerating agents. The blends were tested with a texture analyser to evaluate their mechanical properties, testing the puncture resistance (24 blends) and the tensile strength (15 blends). Scanning electron photomicrographs of some blends were obtained in order to explore the relationship between their components and the mechanical properties. The results indicate that a blend prepared with paper pulp, wheat straw sieved at 2.5 mm and gypsum attained the highest stress resistance and tensile strength. An environmentally controlled experiment was performed on this and another hydromulch in which rice husk substituted wheat straw to evaluate their efficiency for reducing weed seedling emergence, using propagules of four common summer weeds. Compared with the control treatment performed, the hydromulches reduced seedling emergence from 64.6% to 95.9%. In general, the percentage of dead seedlings underneath was greater than that which passed through the barrier, making the hydromulches promising tools for preventing seedling emergence and for managing the weed seed bank in field conditions. Highlights: Mechanical properties of hydromulch blends based on paper pulp were tested. The most resistant blend was dosed with paper pulp, wheat straw and gypsum. The frame was quite compact and showed a suitable punching and traction resistance. The barrier effect of the hydromulches reduced seedling emergence.